Job Categorization based Task Scheduling using QoS in Cloud Environment - Khurana, S; Singh, R K (International Journal of Computer Sciences and Engineering, 2025)
The Cloud computing come into points of interest as a brand new emerging technology which provides personalized QoS guaranteed and trustworthy computing environment for end-customers. In cloud environment the Jobs are planned and accomplish in the constraints. Means of constraints right here is to apply QoS that customers want and balancing among those QoS and impartiality some of the Jobs. Many scheduling algorithms are proposed and executed to fulfill the requirement of cloud computing. Some of the task scheduling algorithms focused on the priority to each task depending on its attributes and then schedule tasks while considering the high priority. Others Jobs scheduling algorithm based upon QoS resourcefully utilized the resources idle time from monitoring the task schedule and timing information. But most of the current scheduling algorithms have not focus on the QoS parameter based upon task computation & communication time. They only examine the inactive time of resources continuously & renew the minimum completion time (MCT) of resources in matrix; but not executed the jobs based upon their job type. The task which demanded high computation resources should executed on high speed CPU and task required communication based resource should be executed on resources with high speed bandwidth. This paper proposed an enhanced QoS based algorithm which also taken into account the task monitoring and job type parameters.